Lipolytic Activity of a Carboxylesterase from Bumblebee (Bombus ignitus) Venom - Yijie Deng; Bo Yeon Kim; Kyeong Yong Lee; Hyung Joo Yoon; Hu Wan; Jianhong Li; Kwang Sik Lee; Byung Rae Jin (Toxins, 2021)
Bee venom is a complex mixture composed of peptides, proteins with enzymatic properties, and low-molecular-weight compounds. Although the carboxylesterase in bee venom has been identified as an allergen, the enzyme’s role as a venom component has not been previously elucidated. Here, we show the lipolytic activity of a bumblebee (Bombus ignitus) venom carboxylesterase (BivCaE). The presence of BivCaE in the venom secreted by B. ignitus worker bees was confirmed using an anti-BivCaE antibody raised against a recombinant BivCaE protein produced in baculovirus-infected insect cells. The enzymatic activity of the recombinant BivCaE protein was optimal at 40 °C and pH 8.5. Recombinant BivCaE protein degrades triglycerides and exhibits high lipolytic activity toward long-chain triglycerides, defining the role of BivCaE as a lipolytic agent. Bee venom phospholipase A2 binds to mammalian cells and induces apoptosis, whereas BivCaE does not affect mammalian cells. Collectively, our data demonstrate that BivCaE functions as a lipolytic agent in bee venom, suggesting that BivCaE will be involved in distributing the venom via degradation of blood triglycerides.